Designing an AI-Integrated ESP Course for Flight Attendant Students in China : A Needs Analysis-Based Approach - Zhou, Yan; Soo, Ruey Shing (Journal of Information Systems Engineering & Management, 2025)
English for Specific Purposes (ESP) plays a pivotal role in flight attendant training, particularly within China’ s vocational education system. However, designing an effective ESP curriculum that meets industry demands remains a significant challenge. This study investigates flight attendant students target needs and their perceptions of AI-integrated ESP instruction. Data were collected from 184 flight attendant students and 4 ESP teachers at a Chinese vocational university through mixed-methods research (questionnaires and interviews). The result revealed that speaking is the core skill and strong student receptiveness toward AI-enhanced learning tools. These insights inform the development of an AI-enhanced ESP curriculum tailored to aviation professionals' communicative requirements.